The Role for Prudence Before Describing Novel Infectious Etiologies for Acute Pancreatitis. The Experience of One Institution Before Describing Influenza B Pancreatitis - Sheikh, Imran; Kanwal, Ayesha; Kyprianou, Annette (JOP. Journal of the Pancreas, 2011)
Context While the majority of acute pancreatitis is secondary to alcohol and gallstones in the developed world, infectious causes are recognized and recent evidence has linked influenza A to acute pancreatitis. Case report We report a patient with acute pancreatitis deemed secondary to influenza B virus; however considering this would be the first reported case, retesting showed that the initial PCR was falsely positive and a system-wide contamination discovered that unearthed other false negatives. Conclusions While research must continue to describe novel infectious etiologies of acute pancreatitis, caution must be exercised before new associations are described. New tests are leading to increasing incidence and prevalence of disease and while such testing generally has high sensitivity and specificity, the role for false results still exists. Image: Extensive peripancreatic inflammatory changes and stranding.